Automated Landing Aid System Based on Visual Detection - TOPÇU, EZGİ; GÜREŞÇİ, EMİN KAAN; SAATÇI, ERTUĞRUL (Fatma Kutlu Gündoğdu, 2025)
Since the invention of the aircraft, the need for runways for takeoff and landing only overland has limited their uses. However, this situation has changed with the invention of aircraft carriers. An aircraft carrier with its flight deck is a warship that acts as an open-sea air base, and it is used to conduct operations in the designated areas. In this work, a prototype landing assistance system is proposed to work alongside landing signal officers (LSOs) on aircraft carriers. The system is based on visual information from the approach and landing phases and includes a voice assistant. The main goal of this system is to assist the LSOs rather than replace them by reducing their workload and minimizing fatigue-related human errors. The system is designed to be activated or deactivated by the LSO as required, ensuring flexibility and adaptability to varying operational needs. The proposed system is designed to be easy to integrate with the equipment already on aircraft carriers while keeping mobility in mind and tested in different weather and lighting conditions in a simulation environment.
Görsel Tespite Dayalı Otomatik İniş Yardım Sistemi
Keywords: Aircraft Landing Systems; Landing Signal Officers; Machine Learning